2013
DOI: 10.1177/0049475513512643
|View full text |Cite
|
Sign up to set email alerts
|

Hypokalaemic periodic paralysis in rural northern India – most have secondary causes

Abstract: Hypokalaemic periodic paralysis (HPP) is a life-threatening condition. Our aim was to study the clinical profile and laboratory parameters of HPP patients and to develop an algorithm to determine the causes of HPP. 84 patients presented with HPP over a 3 year period. 58 (69.0%) were found to have renal tubular acidosis (RTA). The other causes were idiopathic HPP (8 (9.5%)), acute gastroenteritis (4 (4.8%)), suspected primary hyperaldosteronism and familial HPP (2 each (2.4%)) and suspected Gitelman/Bartter Syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 5 publications
2
6
1
Order By: Relevance
“…Table 4 compares this study with the available literature worldwide. [ 9 10 11 12 ] dRTA as a cause of hypokalemic paralysis in our study is similar to various published Indian studies (40%–69%). [ 14 ] dRTA accounts for 93% and pRTA was seen in 7%.…”
Section: Discussionsupporting
confidence: 91%
“…Table 4 compares this study with the available literature worldwide. [ 9 10 11 12 ] dRTA as a cause of hypokalemic paralysis in our study is similar to various published Indian studies (40%–69%). [ 14 ] dRTA accounts for 93% and pRTA was seen in 7%.…”
Section: Discussionsupporting
confidence: 91%
“…these findings had corroborated our findings of atypical manifestations. Whereas the study done by Kumar et al 12 had shown a tendency of hot climate as a trigger, we had found the same in only three cases. We had found hard work or heavy physical labor to be the commonest precipitating factor (Figure 3).…”
Section: Discussioncontrasting
confidence: 77%
“…Thyrotoxic hypokalemic paralysis is common in the Asian population whereas familial periodic paralysis is common in Caucasians. [5][6][7] In India, until recently and excepting few, [8][9][10][11][12][13] no large case series have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…In one series, renal tubular acidosis was the most frequent cause of hypokalemia with paralysis. 30,31 This is particularly the case if there is substantial potassium depletion or if provoked by high-carbohydrate caloric sources. 32 Autoimmune disorders such as Sjögren's syndrome and pernicious anemia should also alert the clinician to the possibility of renal tubular acidosis and potassium depletion as potential causes of hypokalemic paralysis.…”
Section: Figurementioning
confidence: 99%